Prognostic value of combined preoperative prognostic nutritional index and body mass index in HCC after hepatectomy. Issue 8 (August 2017) - Ji, Fei; Liang, Yao; Fu, Shunjun; Chen, Dubo; Cai, XiuQin; Li, Shaoqiang; Peng, Baogang; Liang, Lijian; Hua, Yunpeng
Abstract: Background: Malnutrition and immunological status are associated with survival in many cancers. Prognostic nutritional index (PNI) and body mass index (BMI) are recognized immune-nutritional indices and associated with postoperative outcome in hepatocellular carcinoma (HCC) patients. However, this association is still controversial. Our aim was to determine whether the combination of PNI and BMI is better than either alone in HCC patients' prognosis. Material and methods: Preoperative PNI and BMI, patient demographics, clinical and pathological data from 322 HCC patients were collected and analyzed. Results: Low PNI was correlated with age, cirrhosis, total bilirubin (TBIL) ≥34.2 μmol/L, and recurrence. Likewise, low BMI was associated with TBIL ≥34.2 μmol/L, portal vein tumor thrombi (PVTT), tumor size, tumor differentiation, TNM stage, and recurrence. Multivariate analysis identified TNM stage, PVTT, tumor size, PNI, and BMI as independent predictors of outcome in HCC patients. Low PNI combined with BMI (PNI + BMI) accurately predicted poorer outcome, particularly in patients with TNM stage I HCC. The predictive range of PNI + BMI was more sensitive than that of either alone. Conclusions: preoperative PNI/BMI is an independent predictor of outcome for HCC patients, especially in patients with early stage HCC. Intriguingly, the PNI + BMI combination can enhance the accuracy of prognosis.